PACARAN SEHAT, GENERASI KUAT: STRATEGI, HAMBATAN, DAN PELUANG BAGI GENERASI MILENIAL - Rotua Setiani Sinaga; Sriwati Sihombing; Stanley Sitorus; Tivo Juan Simanjuntak; Yosafat Timothy Limbong; Damayanti Nababan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2022)
This article is a research through Christian Religious Education counseling for adults which discusses